Bovine Lactoferrin Inhibits Dengue Virus Infectivity by Interacting with Heparan Sulfate, Low-Density Lipoprotein Receptor, and DC-SIGN - Chen, Jo-Mei; Fan, Yi-Chin; Lin, Jen-Wei; Chen, Yi-Ying; Hsu, Wei-Li; Chiou, Shyan-Song (International journal of molecular sciences, 2017)
Bovine lactoferrin (bLF) presents in milk and has been shown to inhibit several viral infections. Effective drugs are unavailable for the treatment of dengue virus (DENV) infection. In this study, we evaluated the antiviral effect of bLF against DENV infection in vivo and in vitro. Bovine LF significantly inhibited the infection of the four serotypes of DENV in Vero cells. In the time-of-drug addition test, DENV-2 infection was remarkably inhibited when bLF was added during or prior to the occurrence of virus attachment. We also revealed that bovine LF blocks binding between DENV-2 and the cellular membrane by interacting with heparan sulfate (HS), dendritic cell-specific intercellular adhesion molecule 3-grabbing non-integrin (DC-SIGN), and low-density lipoprotein receptors (LDLR). In addition, bLF inhibits DENV-2 infection and decreases morbidity in a suckling mouse challenge model. This study supports the finding that bLF may inhibit DENV infection by binding to the potential DENV receptors.